An eight‐switch five‐level inverter with zero leakage current. Issue 3 (29th December 2020) - Kumari, Sangeeta; Verma, Arun Kumar; N, Sandeep; Yaragatti, Udaykumar R.; Pota, Hemanshu Roy
Abstract: This paper examines a multilevel transformer‐less grid‐tied inverter topology is proposed for PV applications. Nowadays, transformer‐less inverters are more desirous due to their small filter size, cheaper and higher efficiency. However, the removal of transformer results in the existence of leakage current due to absence of galvanic isolation. The flow of leakage current is the cause of personal safety and deteriorating power quality. A transformer‐less inverter topology is proposed which is able to solve the leakage current issue. Besides, it has the ability to generate the boosted voltage without the need of magnetic component or boosting circuit. It works on the principle of flying/switched capacitor which are able to naturally balance the voltage. Hence, it does not have the limitation of modulation index and no need of complex control scheme to balance or regulate the voltage across an auxiliary capacitor. The performance of the proposed topology is verified by implementing a laboratory prototype which validates the operation and performance of the proposed topology. Results depicting the output voltage, load current and voltage across the auxiliary capacitor are presented for various operating conditions. Moreover, a comprehensive comparison is done, in terms of component count, level and boosting ability of output voltage with leakage current condition.